Generation of reconstituted hemato-lymphoid murine embryos by placental transplantation into embryos lacking HSCs - Jeon, Hyojung (Sci Rep, 2021)
In order to increase the contribution of donor HSC cells, irradiation and DNA alkylating agents have been commonly used as experimental methods to eliminate HSCs for adult mice. But a technique of HSC deletion for mouse embryo for increase contribution of donor cells has not been published. Here, we established for the first time a procedure for placental HSC transplantation into E11.5 Runx1-deficient mice mated with G1-HRD-Runx1 transgenic mice (Runx1(-/-)::Tg mice) that have no HSCs in the fetal liver. Following the transplantation of fetal liver cells from mice (allogeneic) or rats (xenogeneic), high donor cell chimerism was observed in Runx1(-/-)::Tg embryos. Furthermore, chimerism analysis and colony assay data showed that donor fetal liver hematopoietic cells contributed to both white blood cells and red blood cells. Moreover, secondary transplantation into adult recipient mice indicated that the HSCs in rescued Runx1(-/-)::Tg embryos had normal abilities. These results suggest that mice lacking fetal liver HSCs are a powerful tool for hematopoiesis reconstruction during the embryonic stage and can potentially be used in basic research on HSCs or xenograft models.